A novel device for buffy coat collection - Kyle Christian Hardy; Lisa Arrigo; Jennifer Campbell; Jacob Fiedler; Paul Fiedler (BioTechniques, 2025)
Collection of the buffy coat layer from whole blood is critical for detecting rare circulating cells, such as circulating tumor cells (CTCs), which are of great diagnostic and research importance. Conventional methods for buffy coat collection often have low yields, significant erythrocyte contamination, and/or high costs limiting their utility. We developed a novel, multichannel aspiration device that provides efficient buffy coat collection with minimal erythrocyte contamination. This study employed spiked-in myeloma cells to model CTCs and evaluate device performance across a range of CTC concentrations (12, 30, and 300 cells/mL). The device demonstrated high CTC recovery rates, achieving up to 98% at high CTC concentrations and 89% at low concentrations. Immunofluorescent imaging confirmed preservation of cell morphology throughout the collection process. This convenient technology offers the potential of a low-cost alternative for buffy coat collection to be utilized in a wide range of clinical and research applications.